2015
DOI: 10.1002/dc.23269
|View full text |Cite
|
Sign up to set email alerts
|

Pemphigus vulgaris of the cervix: Diagnostic difficulties associated with the Pap test

Abstract: Pemphigus vulgaris (PV) is a rare mucocutaneous disease caused by the abnormal production of antibodies against epithelial cell surface glycoproteins, resulting in loss of cell adhesion and intraepithelial blister formation. Cervical involvement in PV has been poorly reported, and there is little information regarding the criteria about consequential cytological changes identified in a Papanicolaou-stained cervicovaginal smear (Pap smear). Here, we report a case of PV manifesting in the cervix as well as the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Even so, cases of vaginal PV examined by LBC smears of the uterine cervix have been initially misdiagnosed as squamous cell carcinoma (Sq.C.C.) due to the presence of atypical acantholytic cells 7, 8, 9, 10. The cytological features of PV associated with cervical involvement are similar to that seen for PV evaluated by liquid‐based oral smears 6, 8.…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…Even so, cases of vaginal PV examined by LBC smears of the uterine cervix have been initially misdiagnosed as squamous cell carcinoma (Sq.C.C.) due to the presence of atypical acantholytic cells 7, 8, 9, 10. The cytological features of PV associated with cervical involvement are similar to that seen for PV evaluated by liquid‐based oral smears 6, 8.…”
Section: Introductionsupporting
confidence: 55%
“…Unlike the uterine cervical cytology, conventional oral cytology has proven to be of little value because of the high false rates, which can exceed 30% due to fibrotic tissue that prevents exfoliation of the dysplastic cells to the surface of the epithelium 4, 10. To overcome these issues, a new LBC method was developed in which the oral smears were collected through the use of a cytobrush.…”
Section: Discussionmentioning
confidence: 99%
“…In most reported cases, cervical involvement is discovered incidental to vaginal involvement, either as ulcers or as healed white plaques (5). The most common primary presentation attributed to the cervix is of an incidental abnormal pap smear variably misinterpreted as cytologically atypical (atypical squamous cells of undetermined significance, lowgrade squamous intraepithelial lesion, atypcial glandular cells of undetermined significance, high-grade squamous intraepithelial lesion) or malignant (squamous or adenocarcinoma) (2,(6)(7)(8)(9)(10)(11)(12)(13)(14). Rare cases report vaginal discharge, sometimes blood stained (9,13,15).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been shown that there is a significant reduction in expression of desmogleins 1 and 3 in high-grade squamous intraepithelial lesions (SILs) as compared to low-grade SILs and normal cervix [3,10]. Cervical involvement in PV has been investigated in several studies [1,21,23,25,26,35]. Akhyani et al and Kavala et al reported that cervicovaginal Pap smear in 26 % (20/77) and 35 % (12/34) of female patients with PV, respectively, showed changes that were consistent with PV [1,21].…”
Section: Introductionmentioning
confidence: 98%